Presentation and Management of Primary Immune Thrombocytopenia in Children at the King Abdulaziz University Hospital, Jeddah, Saudi Arabia: A Retrospective Study - Nadia M. Fida; Enas A. Hamed; Soad M. Jaber; Salwa A. Al Najjar; Dhuha Al Amawi; Fayza I. Al Siny; Basma Alharthy (Journal of King Abdulaziz University: Medical Sciences, 2021)
Immune thrombocytopenia is a common bleeding disease in pediatrics caused by low antiplatelet antibodies. Its treatment is controversial. This study aims to identify patterns of newly diagnosed immune thrombocytopenia presentation and treatment for children and adolescents admitted to the Pediatric Department at King Abdulaziz University Hospital over a three-year period. All patients who visited the pediatric clinic and were newly diagnosed with immune thrombocytopenia were enrolled. Data from patients’ files were collected and analyzed with respect to demographics, medical history, associated comorbidity, presentation, bleeding incidences (with scores), laboratory investigations, and therapies. Males outnumbered females (56.8% versus 43.2%). Of the 44 participants, 4 were found to have family history of Thrombocytopenia and 21 had previous viral infections. Comorbidities were reported in 7 patients and 5 were anemic. Bleeding degree was mild in 36 and moderate in 8 patients. Disease manifestations were mainly bruising and petechiae (n=30), bleeding gums (n=9), and epistaxis (n=9). Bone marrow aspirations were carried out in 25 patients. Otherwise, treatment modalities included 1) observation (n=5), 2) intravenous immunoglobulin (n=38), 3) corticosteroid (n=11), and 4) anti-D (n=1). Conclusion: the majority of children diagnosed with primary immune thrombocytopenia in the study received unnecessary intravenous immunoglobulin; following international guidelines in management of this disease would likely reduce admission rate, treatment costs, and patient exposure to adverse